(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
This paper investigates the idea of the ‘mediatization’ of Namibian cultures, media power, and degrees of reflexive actor ‘negotiations’ of media institutionalism. It seeks to understand awareness of and reaction to local and global power narratives in relation to actors’ symbolic relationships with media. Research reveals that Namibian youth are often positive regarding the novelty and opportunities that global media off er for identity and lifestyle negotiations. However, it also revealed ontological anxieties about erosion of ‘traditional’ culture on the one hand, and concerns on the other about the absence of representation or recognition of the ‘local’ in global media productions. The Windhoek research on which this paper is based conceptually establishes three reflexive youth orientations and identities toward local/global media power: cultural appropriationist, cultural traditionalist and cultural representationalist. Theories of power and media are contrasted and analysed in relation to these reflexive categories, giving special reference to Lukes (2005). The paper concludes that while media culture today appears to be instrumental in Namibian identity formation and cultural change, social tensions and conflict over matters of culture and power are evident.